Disease control and psychiatric comorbidity among adolescents with chronic medical conditions: a single-centre retrospective study - Kallio Mira; Tornivuori Anna; Miettinen Päivi; Kolho Kaija-Leena; Culnane Evelyn; Sawyer Susan; Kosola Silja (BMJ PUBLISHING GROUP, 2025)
Background To investigate disease control, psychiatric comorbidity, substance use and their possible associations in adolescents with chronic medical conditions before transfer to adult healthcare.
Methods We collected clinical data from the year preceding transfer of care and psychiatric data from the records of the paediatric hospital in Helsinki, Finland (population base 1.7 million). Participants were grouped into three disease and/or adherence control categories (good, some evidence of concern, poor) based on clinical data from the medical records of the year preceding the transfer of care. Participants completed the Adolescent’s Substance Use Measurement Questionnaire before transfer of care and were divided into four risk subgroups accordingly.
Results In total, 253 adolescents (mean age 17.3 years, SD 1.2) from six paediatric subspecialties participated in this study. Disease control and/or adherence were rated as good in 28% (n=70), moderate in 42% (n=105) and poor in 30% (n=76) in the year before participants transferred to adult health services. A quarter of participants had at least one psychiatric diagnosis during adolescence. Adolescents with concomitant psychiatric diagnoses more often had poor disease control of their chronic medical condition than adolescents with only a medical condition (44% vs 26%; n=25 of 59 vs 51 of 194, respectively). More than half of adolescents (56%) were abstinent or used substances infrequently; 10% (n=26) reported hazardous substance use.
Conclusions Psychiatric comorbidity in adolescents with chronic medical conditions is common. Its negative association with disease control and possible substance use should be considered in the transition process to adult health services.